PrintMaster greeting cards deluxe / Broderbund - Br?derbund (Novata, CA Broderbund, 2003)
A desktop publishing package for greeting cards. Includes 650+ fonts, 2,500 sentiments, 13,250+ greeting card templates, and 75,000+ high-quality images. Features integrated photo workshop, share projects via email, card size converter, address book, and event reminder
[disc 1] Install CD -- [disc 2] Program CD -- [disc 3] Art CD 1 -- [disc 4] Art CD-2
1
Keywords: CD.ROM (Children ); Clip art -- Software; Computer graphics -- Software; Greeting cards -- Software; Printing -- Software; Show similar items